PENINGKATAN KEMAMPUAN PEMBELAJARAN EKONOMI DALAM BERWIRAUSAHA DENGAN PAKEM PADA SISWA KELAS XII-S 3 SMA NEGERI 6 MADIUN TAHUN PELAJARAN 2012/2013 - Oerip Pudjiati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
PAKEM model of learning has been determined as learning process which makes use of variative learning method,media and aids. PAKEM model of learning covers encouraging students to summerize,to plan, to excute, and to report activities. Within PAKEM model of learning teacher has to focus on the development of each individual students in such a manner that students get encouraged in learning. Learning instruction should be planned as to fit the students competence, of which every learning process must be ended up with development tasks for every individual student, with results are shown on the class information board to motivate them in gaining better learning performance. The implementation of PAKEM model of learning is attemted to developed students courage and motivation in learning economy to bring about their learning achievement.